STUDENTS’ REFLECTION ON THEIR PERSONAL AND ACADEMIC LIFE DURING EARLY COVID-19 PANDEMIC - Inharjanto, Anselmus; Raharjo, Yohanes Maria Restu Dian (PROGRES PENDIDIKAN, 2024)
Our world has been transformed dramatically by COVID-19 Pandemic as it affected health, economy, politic, social, education, etc. The aim of this research is discovering students’ reflection toward their personal and academic life during early COVID-19 pandmic situations grounded on three zones, namely fear, learning, and growth zones. This descriptive qualitative survey research used questionnaires to gather the data from 187 freshmen in a university in Palembang. The data were analyzed and interpreted by using a thematic analysis consisting of six steps, namely (1) familiarizing with the data, (2) generating initial codes, (3) searching for themes, (4) reviewing themes, (5) defining and naming themes, and (6) producing the report. The research results show that students reflected on their personal and academic life differently when it was reflected based on the three zones. There were also some factors influencing the reflection, namely the transition between senior high school and university and the typically online learning process demanding autonomous learning. Finally, the research suggests that, alongside the society, students might learn how to move gradually one zone to another in order to overcome this global crisis. Therefore, covid-19 pandemic should be perceived then as a lesson learnt.